2003
DOI: 10.1046/j.1365-2648.2003.02562.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships with undergraduate nursing exchange students – a tutor perspective

Abstract: A dialogic tutor-student relationship is important for learning intercultural sensitivity. Tutoring strategies should be developed to assist students' adjustment to the differences in the host culture and to encourage their reflection on personal, experiential and scientific cultural knowledge during their study abroad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…Previous studies have shown that students who participated in global immersion educational programs demonstrated significantly more cognitive growth than those who did not. Additionally, nursing students overcame their ethnocentrism and gained valuable personal, interpersonal and global long-term effects [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that students who participated in global immersion educational programs demonstrated significantly more cognitive growth than those who did not. Additionally, nursing students overcame their ethnocentrism and gained valuable personal, interpersonal and global long-term effects [14]. …”
Section: Introductionmentioning
confidence: 99%
“…However, in some cases communication difficulties can impair the development of intercultural competencies. Occasionally, these difficulties can lead to situations where students and scholars start to totally withdraw from interactions and ultimately become isolated (Koskinen & Tossavainen, 2003;Ruddock & Turner de, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Publications resulting from such endeavors would increase the academic credibility of the collaborating universities. Once universities “adopt” another university, international elective placements for nursing students from both Ghana and Uganda would be exposed to opportunities for experiences of working with high‐tech equipment that were not available in their respective countries (Koskinen & Tossavainen, 2003). This could contribute significantly in reducing the need for qualified nurses to leave their country to seek employment overseas.…”
Section: Challenges and Possible Solutionsmentioning
confidence: 99%